Prediction of The Energy Required for Ho:YAG Laser Lithotripsy of Urinary Stones: Energy Required For Laser Lithotripsy - Selmi, Volkan; Oztekin, Unal; Caniklioglu, Mehmet; Isikay, Levent (Urology Journal, 2021)
Purpose: In this study, we aimed to find a more accurate predicting constant value of energy per mm3xHounsfield Unit (HU) to ablate urinary stones by endoscopic stone treatment. Material And Methods: The files of 142 patients who underwent rigid or flexible ureteroscopic laser lithotripsy in our clinic between December 2018 and March 2020 were evaluated retrospectively. Total energy administered for the ablation of the stone was obtained from the registry of the Ho:YAG laser and recorded to the follow-up forms. The constant value was calculated for each stone, and the final mean value was figured out by calculation of the mean of all constant values. Results: The study was conducted with 142 patients; 102 males and 40 females. The mean age of the population was 46.61 ± 14.58 years. The number of stones was 1.27 ± 0.67. The mean constant value of energy needed per mm3xHU for urinary stones was 22.87 milliwatt. Conclusion: This study was conducted to report a predictive constant value and is the very first study evaluating the energy prediction per mm3xHU. The data of the study showed that the constant value is 22.87 mW/mm3xHU. Urologists may estimate the required energy and plan the surgery according to the outcomes of the study. As a future aspect of our study, the constant value may represent predictive information about the time and accuracy of the operation.